2019
DOI: 10.1007/s10827-019-00729-1
|View full text |Cite
|
Sign up to set email alerts
|

Introducing double bouquet cells into a modular cortical associative memory model

Abstract: We present an electrophysiological model of double bouquet cells and integrate them into an established cortical columnar microcircuit model that has previously been used as a spiking attractor model for memory. Learning in that model relies on a Hebbian-Bayesian learning rule to condition recurrent connectivity between pyramidal cells. We here demonstrate that the inclusion of a biophysically plausible double bouquet cell model can solve earlier concerns about learning rules that simultaneously learn excitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Model networks with negative synaptic weights have been shown to be functionally equivalent to those with both excitatory and inhibitory neurons with only positive weights (Parisien et al, 2008). In the context of this particular model microcircuit and learning rule, this was explicitly and conclusively demonstrated by the addition of double bouquet cells (Chrysanthidis et al, 2019).…”
Section: Neuron Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…Model networks with negative synaptic weights have been shown to be functionally equivalent to those with both excitatory and inhibitory neurons with only positive weights (Parisien et al, 2008). In the context of this particular model microcircuit and learning rule, this was explicitly and conclusively demonstrated by the addition of double bouquet cells (Chrysanthidis et al, 2019).…”
Section: Neuron Modelmentioning
confidence: 89%
“…In this model, we focus on layers 2/3, as its high degree of recurrent connectivity (Thomson et al, 2002;) supports attractor function. The high fine-scale specificity of dense stellate cell and double-bouquet cell inputs (DeFelipe et al, 2006;Chrysanthidis et al, 2019) enable strongly coding subpopulations in the superior layers of functional columns. This fits with the general observation that layers 2/3 are more input selective than the lower layers (Crochet and Petersen, 2009;Sakata and Harris, 2009) and thus of more immediate concern to our computational model.…”
Section: Interarea Connectivitymentioning
confidence: 99%
“…For simplicity, we assume that Item and Context networks are located at a substantial distance accounting for the reduced internetwork connection probabilities ( Table 3 ). Each network follows a cortical architecture with modular structure compatible with previous spiking implementations of attractor memory networks ( Lansner, 2009 ; Lundqvist et al, 2011 ; Tully et al, 2014 , 2016 ; Fiebig and Lansner, 2017 ; Chrysanthidis et al, 2019 ; Fiebig et al, 2020 ), and is best understood as a subsampled cortical layer 2/3 patch with nested hypercolumns (HCs) and minicolumns (MCs; Fig. 1 A ).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, double bouquet cells shown in Figure 1 A are not explicitly simulated, but their effect is nonetheless expressed by the BCPNN rule. A recent study based on a similar single-network architecture (i.e., with the same modular organization, microcircuitry, conductance-based AdEx neuron model, cell count per MC and HC) demonstrated that learned mono-synaptic inhibition between competing attractors is functionally equivalent to the disynaptic inhibition mediated by double bouquet and basket cells ( Chrysanthidis et al, 2019 ). Parameters characterizing other neural and synaptic properties including BCPNN can be found in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…These LBCs and MCs have large clusters of axons that extend not only across the layers but also across multiple columns. The LBCs have electrophysiological properties similar to those of PCs, meaning that their neuronal parameters are the same as those of PCs in the respective layers (Chrysanthidis et al, 2019). Neurons were distributed over the five cell types in each layer based on estimates from the literature (Markram et al, 2004).…”
Section: Neural Network Modelmentioning
confidence: 99%